2021
DOI: 10.1177/01945998211035097
|View full text |Cite
|
Sign up to set email alerts
|

Sinus Radiological Findings in General Asymptomatic Populations: A Systematic Review of Incidental Mucosal Changes

Abstract: Objective To determine the range of incidental mucosal changes in a general sinonasally asymptomatic population on radiology. Data Sources Medline (1996-present) and Embase (1974-present) were searched on March 14, 2020, to identify articles that reported radiological sinus mucosal findings in asymptomatic population groups. Bibliographic search of included studies was conducted to identify additional articles. Review Methods The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
(105 reference statements)
0
13
0
Order By: Relevance
“…In 38.9% of the sinuses, this swelling was above 2 mm. This is a much higher prevalence than the reported 17.73% (95% CI, 8.67–29.08%) in the systematic review by Razi et al [ 29 ], scrutinizing 16.966 sino-nasal asymptomatic adults and children. They emphasized that this outcome was affected by confounding factors such as associated periodontal disease in dentate subjects, different type of imaging protocols, seasonal influence, the lack of standardization of the measurement method, and the measurement location.…”
Section: Discussionmentioning
confidence: 60%
“…In 38.9% of the sinuses, this swelling was above 2 mm. This is a much higher prevalence than the reported 17.73% (95% CI, 8.67–29.08%) in the systematic review by Razi et al [ 29 ], scrutinizing 16.966 sino-nasal asymptomatic adults and children. They emphasized that this outcome was affected by confounding factors such as associated periodontal disease in dentate subjects, different type of imaging protocols, seasonal influence, the lack of standardization of the measurement method, and the measurement location.…”
Section: Discussionmentioning
confidence: 60%
“…15 A recent systematic review reported that individuals without sinonasal symptoms and without CRS have a mean Lund-Mackay score between 1.8 and 2.24, with mucous retention cysts found in 13% and ≥2 mm of maxillary mucosal thickening present in 17.73%. 19 However, these Lund-Mackay score results reflect the sinus-wide radiographic profile of non-CRS patients and do not provide insights for sinus-by-sinus comparison of CRS versus non-CRS radiographic findings. The finding that 17.73% of asymptomatic non-CRS individuals have ≥2 mm mucosal thickening in the maxillary sinuses does not exclude the possibility that, for example, a medically recalcitrant CRS patient who is being actively treated with topical corticosteroids, could have less than 2 mm of mucosal thickening in a maxillary sinus.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, these findings did not address any of the other paranasal sinuses, where mucosal thickening is typically found to be less pronounced than in the maxillary sinuses in CRS 15 . A recent systematic review reported that individuals without sinonasal symptoms and without CRS have a mean Lund‐Mackay score between 1.8 and 2.24, with mucous retention cysts found in 13% and ≥2 mm of maxillary mucosal thickening present in 17.73% 19 . However, these Lund‐Mackay score results reflect the sinus‐wide radiographic profile of non‐CRS patients and do not provide insights for sinus‐by‐sinus comparison of CRS versus non‐CRS radiographic findings.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, numerous studies have demonstrated significant limits of sinus imaging that negatively impact facial pain evaluations. First, multiple studies have shown a high prevalence of incidental sinus abnormalities on 15% to 42% of head/sinus CTs, [36][37][38] and 30% to 85% of MRIs. 36,39 More specifically, patients undergoing CT for non-sinogenic headaches have abnormal sinus findings in 29% to 80% of cases.…”
Section: Discussionmentioning
confidence: 99%